The Nuclear Tipping Point : Why States Reconsider Their Nuclear Choices - Reiss, Mitchell; Einhorn, Robert J.; Campbell, Kurt M., 1957- (Book collections on Project MUSE., 2004)
More than half a century after the advent of the nuclear age, is the world approaching a tipping point that will unleash an epidemic of nuclear proliferation? Today many of the building blocks of a nuclear arsenal--scientific and engineering expertise, precision machine tools, software, design information--are more readily available than ever before. The nuclear pretensions of so-called rogue states and terrorist organizations are much discussed. But how firm is the resolve of those countries that historically have chosen to forswear nuclear weapons? A combination of changes in the international.